2015
DOI: 10.1111/jgs.13648
|View full text |Cite
|
Sign up to set email alerts
|

Using a Clinical Surveillance System to Detect Drug‐Associated Hypoglycemia in Nursing Home Residents

Abstract: Background/Objectives Hypoglycemia is a common adverse drug event (ADE) frequently associated with temporary harm in the nursing home (NH) setting. Reports from the Office of the Inspector General and the U.S. Department of Health and Human Services recommend the need for increased surveillance of drug-associated hypoglycemia events. The objective of this study was to test if a clinical surveillance system could be used to detect drug-associated hypoglycemia events and determine their incidence in NH residents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 17 publications
0
10
0
1
Order By: Relevance
“…CPs also received clinical decision support (CDS) alerts that were formulated within an electronic health record (EHR)‐agnostic platform (TheraDoc®, Premier, Inc., Charlotte, NC). TheraDoc® is a clinical surveillance system that contains many predeveloped alerts and allows for customizable alerts, “EZ alerts,” to be developed by local users 21‐23 . Alerts were developed to detect potentially inappropriate prescribing (defined by CMS as excessive dose, lack of monitoring, and therapeutic duplication) and recommendations in the Office of Inspector General Report 4,20 .…”
Section: Methodsmentioning
confidence: 99%
“…CPs also received clinical decision support (CDS) alerts that were formulated within an electronic health record (EHR)‐agnostic platform (TheraDoc®, Premier, Inc., Charlotte, NC). TheraDoc® is a clinical surveillance system that contains many predeveloped alerts and allows for customizable alerts, “EZ alerts,” to be developed by local users 21‐23 . Alerts were developed to detect potentially inappropriate prescribing (defined by CMS as excessive dose, lack of monitoring, and therapeutic duplication) and recommendations in the Office of Inspector General Report 4,20 .…”
Section: Methodsmentioning
confidence: 99%
“…Telehealth has been a useful intervention to optimize health care in a number of SNF environments. Surveillance of dangerous lab values and automated clinical decision support for NH residents have used telehealth to trigger automated alerts in electronic health records (Culley, Perera, Marcum, Kane-Gill, & Handler, 2015;Kane-Gill, Achanta, Kellum, & Handler, 2016;Kane-Gill et al, 2017). Others have successfully used off-hour telemedicine consultation as opposed to on-call NH providers to reduce preventable NH to ED transfers (Grabowski & O'Malley, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Data from a recent study showed that insulin caused 98.7% of hypoglycemia alerts in four NHs [68]. The results of these studies help to compare our study results since we investigated ADEs caused by all the above medications.…”
Section: Personmentioning
confidence: 84%
“…In Pennsylvania also, a recent retrospective cohort study reported an incidence of drug-induced hypoglycemia of 12.8%, and insulin was associated with the majority (98.7%) of the cases. [68]. An Italian study found a fall incidence rate of 1.38 per 100 resident-months and 48.1% of these falls resulted in injuries.…”
Section: Personmentioning
confidence: 99%
See 1 more Smart Citation